Effectiveness of Complete Systematic Land Registration: Role of Community and Village Government - Julius T. Mandjo; Dolot Alhasni Bakung; Mohamad Hidayat Muhtar; Sofyan Piyo; Fitran Amrain (Universitas Negeri Gorontalo, 2026)
Kuliah Kerja Nyata (KKN) thematic at Gorontalo State University in Tupa Village, North Bulango District, Bone Bolango Regency, was held to address fundamental land issues that still often cause disputes due to weak administration, unclear ownership, and a lack of public understanding of land law. Through legal counseling focused on implementing the complete systematic land registration (PTSL) Program in accordance with ATR/BPN Regulation Number 6 of 2018, this activity aims to increase community legal awareness, strengthen village government capacity, and foster synergies among the community, government, and related institutions. The implementation method is carried out in a participatory manner through material exposure, interactive discussions, and direct clarification of field problems, such as delays in issuing certificates, differences in understanding of wills and grants, obstacles to land measurement in hilly areas, and abrasion issues on river banks. The results of the activity showed increased public understanding of the importance of land certificates as an instrument of legal protection and economic access, increased public confidence in government institutions, and a shift in legal culture towards administrative order. This activity also affects students who gain empirical experience in understanding law as a social reality. Thus, this legal counseling not only increases public awareness but also strengthens sustainable development at the village level.